BEHAVIORS IN AND BARRIERS TO EXERCISE IN AMMARTPANICHANUKUL SCHOOL STUDENTS IN KRABI PROVINCE - Pakdeevanich, Kittiya; Tengku Sulaiman , Raja Syed; Choeychom, Kongkiat (Academic Journal of Thailand National Sports University, 2020)
The purpose of this study was to find out the behaviors in and the barriers to exercise in Ammartpanichnukul school students in Krabi Province. The samples of this study were 360 secondary-school-level-1-to-6 students. The samples were selected utilizing Multi-statge random sampling method consisting of stratified and cluster random sampling. The instrument used to collect the data was a questionnaire consisting of checklist, rating scale and open ended questionnaires. The total content validity and reliability of the questionnaire were 0.95 and 0.83 respectively. The statistics for the data analysis were frequency and percentage. Based on the analysis of the gathered data, the two findings were: 1) Most of male students often exercised with their friends on Friday, while female students exercised with their family on Saturday. They usually exercised after school 1–2 days a week at the public parks near their residence for 20–30 minutes. The main purpose of their exercise was health development. They always developed their circulatory and respiratory systems by jogging and walking and improved their body flexibility by stretching exercise. The male and female students enhanced their muscular strength using weight training equipment and body weight respectively. The stretching exercise was utilized in both warm-up and cool-down activities less than 5 minutes for male and 5–10 minutes for female students. 2) Most of students had exercise barriers at a high level, but male students in secondary school level 1 had such barriers at a moderate level. This study was also found that the tiredness of learning activities was the exercise barrier of male students in secondary school level 1 and 3, and the laziness was the barrier of female students in both secondary school levels. In addition, the weariness as mentioned was also the exercise barrier of both secondary school level 2 and 6 students. Apart from that, this study was also found that the time limitation and laziness were the exercise barriers of secondary school level 4 and 5 students respectively.